2016
DOI: 10.1021/acschembio.6b00243
|View full text |Cite
|
Sign up to set email alerts
|

A Chemical Biology Approach to Reveal Sirt6-targeted Histone H3 Sites in Nucleosomes

Abstract: As a member of a highly conserved family of NAD+-dependent histone deacetylases, Sirt6 is a key regulator of mammalian genome stability, metabolism, and life span. Previous studies indicated that Sirt6 is hardwired to remove histone acetylation at H3K9 and H3K56. However, how Sirt6 recognizes its nucleosome substrates has been elusive due to the difficulty of accessing homogenous acetyl-nucleosomes and the low activity of Sirt6 toward peptide substrates. Based on the fact that Sirt6 has an enhanced activity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 47 publications
3
74
0
Order By: Relevance
“…characterized as a highly specific H3 deacetylase that targets Lys-9 (H3K9), Lys-56 (H3K56), and Lys-18 (H3K18) (Fig. 2) (86,121,122,140,171), as confirmed by Wang et al through a novel approach to generate nucleosomes specifically acetylated on a single specific site (191). It has been hypothesized that, under oxidative and nitrosative stress, SIRT6 activity can be regulated via reactive nitrogen species-mediated posttranslational modifications (71).…”
Section: Redox Regulation Of Sirt6 In Vascular Protectionmentioning
confidence: 88%
“…characterized as a highly specific H3 deacetylase that targets Lys-9 (H3K9), Lys-56 (H3K56), and Lys-18 (H3K18) (Fig. 2) (86,121,122,140,171), as confirmed by Wang et al through a novel approach to generate nucleosomes specifically acetylated on a single specific site (191). It has been hypothesized that, under oxidative and nitrosative stress, SIRT6 activity can be regulated via reactive nitrogen species-mediated posttranslational modifications (71).…”
Section: Redox Regulation Of Sirt6 In Vascular Protectionmentioning
confidence: 88%
“…Recently, using a novel approach to generate nucleosomes that are specifically acetylated on a single defined site, Wang and colleagues definitively confirmed the high efficiency and selectivity of SIRT6 in deacetylating its previously described substrates H3K9ac and H3K18ac. In addition, they showed that SIRT6 can also deacetylate nucleosomal H3K27ac, a chromatin mark associated with transcriptional enhancer elements, suggesting potential functions of SIRT6 in enhancer-regulated gene expression programs [14]. Interestingly, the in vitro deacetylation of histone peptides by SIRT6 can be activated up to 35-fold fold by free fatty acids (FFAs; e.g., myristic acid), suggesting that in vivo , efficient deacetylation of known or novel SIRT6 substrates could depend on endogenous FFA activators that fluctuate with metabolic conditions [15].…”
Section: Insights Into Biochemical Substrates and Physiologic Functiomentioning
confidence: 99%
“…They showed that SIRT6 removes long-chain octenoyl-groups on H3K9, H3K18, and H3K27 (and with weaker activity, on H3K4 and H3K23), but was unable to de-octenoylate these residues when acylated free H3 histones or acylated H3-H4 tetramers were used as substrates. Thus, both the deacetylase and long-chain defatty-acylase activities of SIRT6 appear to be much more active on histones in the physiologic context of nucleosomal structure [14]. …”
Section: Insights Into Biochemical Substrates and Physiologic Functiomentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Thea bility to generate site-specifically lipidated proteins in vivo will greatly facilitate the investigation of the complicated network of membranes and lipidated proteins involved in basic cellular function and human diseases.U aas bearing simple alkyl, alkyl thiol ether, or halo-and alkene-terminated alkyl side chains have been genetically incorporated into proteins, [9] yet their binding with HSA has not been investigated and they may not be ideal candidates for HSA binding due to their insufficient length or terminal derivatization. [8] Thea bility to generate site-specifically lipidated proteins in vivo will greatly facilitate the investigation of the complicated network of membranes and lipidated proteins involved in basic cellular function and human diseases.U aas bearing simple alkyl, alkyl thiol ether, or halo-and alkene-terminated alkyl side chains have been genetically incorporated into proteins, [9] yet their binding with HSA has not been investigated and they may not be ideal candidates for HSA binding due to their insufficient length or terminal derivatization.…”
mentioning
confidence: 99%